Postprandial response to a fat tolerance test in young adults with a paternal history of premature coronary heart disease - the EARS II study - TIRET, L; GERDES, C; MURPHY, M. J; DALLONGEVILLE, J; NICAUD, Y; O'REILLY, D. S. J; BEISIEGEL, U; DE BACKER, G (European journal of clinical investigation, 2000)
Background The European Atherosclerosis Research Study (EARS) I had shown that fasting plasma concentrations of apolipoprotein B (apo B) and triglycerides were the most discriminant variables between offspring with a paternal history of coronary heart disease (CHD) and controls. The EARS II study was undertaken to investigate whether a paternal history of CHD was associated with differences in postprandial lipemia. Design Male subjects with a paternal history of CHD (cases, n = 407) and age‐matched male controls (n = 415) were recruited from 14 European universities. All subjects had an oral fat tolerance test. Results In the sample as a whole, the postprandial triglyceride responses did not significantly differ between the two groups. However, in the upper tertile of fasting triglycerides, cases displayed a higher area under the curve (5.71 vs. 4.49 mmol.h L−1, P < 0.001), a higher peak (1.76 vs. 1.43 mmol L−1, P < 0.001) and a more delayed time to peak (3.15 vs. 2.91 h, P < 0.05) than controls. In the upper tertile, fasting apo B levels (P < 0.05) and triglyceride area under the curve (P = 0.002) significantly discriminated cases from controls in a multivariate analysis. Cases had also higher Lp C‐III:B levels at 4 h than controls (11.2 vs. 9.9 mg dL−1, P < 0.01) and this difference remained significant after adjustment for apo B and triglyceride levels. Conclusions These results indicate that in subjects with a moderate elevation of fasting triglycerides, an impaired postprandial response to a fat load constitutes an early biological expression of a paternal history of premature CHD.